Towards a comprehensive climate impacts assessment of solar geoengineering - Irvine, Peter J.; Kravitz, Ben; Lawrence, Mark G.; Gerten, Dieter; Caminade, Cyril; Gosling, Simon N.; Hendy, Erica; Kassie, Belay; Kissling, W. Daniel; Muri, Helene; Oschlies, Andreas; Smith, Steven J. (Wiley, 2017)
Despite a growing literature on the climate response to solar geoengineering – proposals to cool the planet by increasing the planetary albedo – there has been little published on the impacts of solar geoengineering on natural and human systems such as agriculture, health, water resources, and ecosystems. An understanding of the impacts of different scenarios of solar geoengineering deployment will be crucial for informing decisions on whether and how to deploy it. Here we review the current state of knowledge about impacts of a solar geoengineered climate and identify major research gaps. We suggest that a thorough assessment of the climate impacts of a range of scenarios of solar geoengineering deployment is needed and can build upon existing frameworks. However, solar geoengineering poses a novel challenge for climate impacts research as the manner of deployment could be tailored to pursue different objectives making possible a wide range of climate outcomes. We present a number of ideas for approaches to extend the survey of climate impacts beyond standard scenarios of solar geoengineering deployment to address this challenge. Reducing the impacts of climate change is the fundamental motivator for emissions reductions and for considering whether and how to deploy solar geoengineering. This means that the active engagement of the climate impacts research community will be important for improving the overall understanding of the opportunities, challenges and risks presented by solar geoengineering.